THINK AGAIN: ADDING VALUE. Issue 3 (10th September 2013) - Davis, Evan; Kay, John
Abstract : In this edited article from Summer 1990, Evan Davis andJohn Kay argue a compelling case for added value as a key measure of organisational success.